Hesperetin exerts apoptotic effect on A431 skin carcinoma cells by regulating mitogen activated protein kinases and cyclins - Smina, T P; Mohan, A; Ayyappa, K A; Sethuraman, S; Krishnan, U M (Cellular and Molecular Biology, 2015)
Dietary agents and phytochemicals have been utilised for the management of cancer for many years. Hesperetin, a dietary flavonoid found abundantly in citrus fruits, was evaluated for its cytotoxic and pro-apoptotic activities in A431 human skin carcinoma cells. Effect of hesperetin in regulating MAPK (Mitogen-Activated Protein Kinase) signalling pathway and levels of various cyclins and other downstream apoptotic proteins were investigated. Its critical role in regulating other apoptotic proteins especially p21, Bcl-2 and Bax were also assessed. Hesperetin stimulated alterations in MAPK (Mitogen-Activated Protein Kinase) signalling pathway by modulating the expression levels of ERK (Extracellular signal Regulated Kinase), JNK (c-Jun NH2-terminal Kinase) and p38; thereby induced apoptosis in A431 cells. Hesperetin regulated the levels of cyclin A2, B1, D1, D3 and E1. It also modulated the levels of various proteins involved in apoptotic pathway especially p21, Bcl-2 and Bax. The study revealed the efficiency of hesperetin against human skin carcinoma cells and proposed its mechanism of action; there by opens up new avenues for the use of this dietary flavonoid against skin malignancies.